Pengaruh Pelatihan, Disiplin Kerja, dan Budaya Organisasi Terhadap Komitmen Organisasi Pegawai PT. PLN (Persero) Area Tanjungpinang - Intan Maizah Ela Yani; Myrna Sofia; Nurhasanah Nurhasanah (Program Studi Manajemen Fakultas Ekonomi UMRAH, 2018)
This study aims to determine the effect of training, work discipline and organizational culture on the organizational commitment of employees of PT. PLN (Persero) Tanjungpinang Area. The research method used is descriptive statistical method with a quantitative approach. Data collection techniques are carried out by observation and questionnaire. The number of research samples used was 74 respondents. Analysis of the data used is multiple linear regression analysis, hypothesis testing in the form of T test and F test and analysis of the coefficient of determination. The research conducted resulted in training having a significant effect on the organizational commitment of employees of PT. PLN (Persero) Tanjungpinang Area because the value of t arithmetic> t table or 23,057> 1,994 and the significance value produced 0,000 <0,05. Work Discipline has a significant effect on the organizational commitment of employees of PT. PLN (Persero) Tanjungpinang Area because the value of t count> ttable or 2.649> 1.994 and the significance value produced 0.010 <0.05. Organizational culture does not affect the organizational commitment of employees of PT. PLN (Persero) Tanjungpinang Area because the value of t count <t table or -1.424> 1.994 and the significance value produced is 0.159> 0.05.